Strategy for Writing Scientific Research among Students in Department of Arabic - Latifatul Mahbubah; Sutaman Sutaman; Syuhadak Syuhadak (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2021)
Based on the existing data and studies, it was found that the rate of college students in Indonesia finishing their study on time is below 70%. Even in some universities, the rate of college students in Indonesia finishing their study on time did not reach 65%. Conversely, the rate of finishing study of students at IAIN Madura, East Java, Indonesia was quite high, especially students of the Department of Arabic. From the results of interviews and observations, it was found that they have a special strategy in thesis writing so that they can finish the study on time. Therefore, the aim of this research was to uncover the thesis writing strategy among the students of the Department of Arabic at IAIN Madura. This research was a qualitative case study which reveals the thesis writing strategy among the students of the Department of Arabic at IAIN Madura. The results showed that the student thesis writing strategy consisted of six strategies, namely: planning, data collection, content preparation, translation, evaluation, and revision.